ON THE CONCEPT OF REPRESENTATIVE SPACE PHASOR IN THE DYNAMIC MODEL OF THE THREE-PHASE INDUCTION MACHINE (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2023)
In the paper, based on the linear dynamic behavior models of the electrical and magnetic subsystems of the induction machine with three-phase symmetrical stator winding and polyphase rotor winding (cage type) in short circuit, the values ​​are represented, in the complex plane confused with the cross-sectional plane of the machine and the instantaneous polar angular positions of the amplitudes of the progressive (spinning) plane waves of the instantaneous resultant solenations of the machine windings, and correspondingly, the spatial phasors representative of the instantaneous electrical circuit scalar quantities of the stator phase windings and rotor equivalents of the machine are defined. The metric (length and orientation) of these representative spatial phasors allows their physical significance to be revealed.
Keywords: REPRESENTATIVE SPACE PHASOR; THREE-PHASE INDUCTION MACHINE; DYNAMIC MODEL